2017
DOI: 10.1002/aic.16029
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of circulating fluidized beds systems for post‐combustion CO2 capture via temperature swing adsorption

Abstract: The technology of circulating fluidized beds (CFBs) is applied to temperature swing adsorption (TSA) processes for post-combustion CO 2 capture employing a commercial zeolite sorbent. Steady state operation is simulated through a one-dimensional model, which combines binary adsorption with the CFB dynamics. Both single step and multi-step arrangements are investigated. Extensive sensitivity analyses are performed varying the operating conditions, in order to assess the influence of the main operational paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 34 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…Fluidized bed reactors are expected to fulfill both requirements. Various continuous CO 2 capture systems have been developed on the basis of a fluidized bed. For a better CO 2 capture performance, the reactor must also address the following points: (i) a sufficient gas-sorbent contact time and (ii) adjustable sorbent circulation between adsorber and desorber.…”
Section: Introductionmentioning
confidence: 99%
“…Fluidized bed reactors are expected to fulfill both requirements. Various continuous CO 2 capture systems have been developed on the basis of a fluidized bed. For a better CO 2 capture performance, the reactor must also address the following points: (i) a sufficient gas-sorbent contact time and (ii) adjustable sorbent circulation between adsorber and desorber.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the aforementioned challenges, the multistage fluidized bed configuration remains promising for adsorptionbased CO 2 capture and a number of pilot scale studies have already been completed with such configuration. 13,34,77 Another approach to reduce the back mixing uses multiple isolated circulating fluidized bed reactors as proposed by Zanco et al 78 The modeling work suggested that this configuration is close to the counter-current multistage adsorption as discussed earlier. However, to achieve the desired separation and minimized energy penalty, the multistage counter current reactor configuration with a single regenerator is still preferred.…”
Section: Mass Transfermentioning
confidence: 98%
“…Another approach to reduce the back mixing uses multiple isolated circulating fluidized bed reactors as proposed by Zanco et al The modeling work suggested that this configuration is close to the counter-current multistage adsorption as discussed earlier. However, to achieve the desired separation and minimized energy penalty, the multistage counter current reactor configuration with a single regenerator is still preferred.…”
Section: Reactor Configurationsmentioning
confidence: 99%
“…Besides reducing the computational effort of the MBTSA simulations, another reason for considering dried flue gas is to avoid limiting the choice of the adsorbent to those material having low affinity towards water, such as activated carbons. For the purpose of this study, it was therefore possible to employ a Zeolite 13X, which is suitable for the NGCC case, for its high CO 2 adsorption capacity at low CO 2 partial pressures and high CO 2 /N 2 selectivity (Zanco et al, 2018, Hefti et al, 2015, Lillia et al, 2018, Merel et al, 2008. A sample of Zeolite 13X, pelletized into spherical particles of 700 µm diameter, was purchased by CWK, Germany.…”
Section: The Adsorbent Materialsmentioning
confidence: 99%